Criteria for the Effectiveness of Surgical Treatment for Primary Open-Angle Glaucoma - Abdurakhmonovich, Boboev Saidavzal; Saidavzalzoda, Abdurakhmonova Sitora (American Journal of Biology and Natural Sciences, 2025)
This investigation evaluates measurable indicators that define the success of surgical management in primary open-angle glaucoma. The analysis focuses on intraocular pressure regulation, structural optic nerve stability, functional preservation of visual fields, postoperative complications, and long-term sustainability of the achieved therapeutic effect. The study aims to identify evidence-based benchmarks that allow clinicians to objectively determine whether surgical intervention provides durable control of disease progression and functional visual protection. This study examines comprehensive indicators that determine the success of operative strategies for primary open-angle glaucoma, emphasizing measurable parameters that reflect functional steadiness, structural conservation, and durable intraocular fluid regulation. The analysis integrates pressure behavior, nerve tissue changes, field performance, safety profile, and long-term therapeutic consistency to form an expanded evaluative framework. These components together describe the capacity of surgical intervention to halt pathological advancement, stabilize optic pathways, and sustain useful vision in individuals who do not achieve adequate control through nonoperative measures.